1990
DOI: 10.1016/0020-7292(90)91019-m
|View full text |Cite
|
Sign up to set email alerts
|

True rupture/scar dehiscence in delivery following prior section

Abstract: Fear of uterine rupture has led to the widespread practice of 'Once a section, always a section'. Between 1972 and 1982, 1498 patients with one or more previous cesarean sections were delivered at University College Hospital, Galway. Trial of labor was undertaken in 844 patients, while the remaining 654 patients underwent repeat elective section because they had two or more prior sections. Eight true ruptures and 22 scar dehiscences were found. Regional analgesia and oxytocin did not significantly affect the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Repeat Caesarean section is mandatory after a CCS due to an incidence of uterine rupture in future pregnancies of 2-8% (compared to 0.5% for LUSCS) (1,5,6). Not all cases of uterine rupture after CCS will be prevented by repeat elective Caesarean section since rupture of the classical scar can occur prior to elective Caesarean section, either antenatally (as with 1 of the women in this study) or in early labour before Caesarean section can be effected (7)(8)(9).…”
Section: Discussionmentioning
confidence: 85%
“…Repeat Caesarean section is mandatory after a CCS due to an incidence of uterine rupture in future pregnancies of 2-8% (compared to 0.5% for LUSCS) (1,5,6). Not all cases of uterine rupture after CCS will be prevented by repeat elective Caesarean section since rupture of the classical scar can occur prior to elective Caesarean section, either antenatally (as with 1 of the women in this study) or in early labour before Caesarean section can be effected (7)(8)(9).…”
Section: Discussionmentioning
confidence: 85%
“…We realize that many questions remain unanswered, the main one being: is it safe for a woman in whom a dehiscence has been found to become pregnant? Some authors have suggested the surgical correction of the uterine scar21, 22, but no proof of its necessity or utility has been found. The prevalence of scar dehiscence (in the present series 2/33 or 6%) is much higher than the reported risk of uterine rupture (0.4%)7.…”
Section: Discussionmentioning
confidence: 99%
“…Labor and vaginal delivery are usually not affected by lower segment 'window' ( 3 ) . Meehan et al ( 5 ) reported two patients with bloodless, unrepaired dehiscence who had subsequent elective cesareans with no evidence of scar dehiscence. Although elective repeated cesarean delivery is recommended, vaginal delivery has been reported after nonrepair of such lower segment separation (8).…”
Section: Discussionmentioning
confidence: 99%
“…Obstetrical management policy allowed each patient with one previous lower uterine segment scar a trial of labor, except when there were indications for a repeat cesarean section. Trial of labor was defined as induced or spontaneous labor in a patient with prior cesarean section (5). Induction and stimulation methods used in labor were artificial rupture of membranes and breast stimulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation